Peaches : a novel - Anderson, Jodi Lynn. (New York : HarperTrophy, 2006)
Three teenaged girls from very different backgrounds, thrown together to pick peaches in a Georgia orchard, spend a summer in pursuit of the right boy, the truest of friends, and the perfect peach.
Young Adult
Keywords: Interpersonal relations -- Juvenile fiction; Farm life -- Georgia -- Juvenile fiction; Problem families -- Juvenile fiction; Peach -- Juvenile fiction; Interpersonal relations -- Fiction; Farm life -- Georgia -- Fiction; Family problems -- Fiction; Peach -- Fiction; Georgia -- Juvenile fiction; Georgia -- Fiction